Arahan Mitigasi Bencana Banjir Rob di Kawasan Pesisir Kecamatan Balusu Kabupaten Barru - Muh Nur Imam; Rudi Latief; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
The purpose of this study is to identify the level of tidal flood disaster vulnerability, to identify the level of tidal flood disaster vulnerability, and to formulate tidal flood mitigation directions in the Coastal Area, Balusu District, Barru Regency. This research requires data, namely spatial data, quantitative data and qualitative data. The method used in this research is a quantitative approach where this method has the characteristics of an approach using quantitative data analysis. The analytical method used in the form of vulnerability analysis, vulnerability analysis and descriptive analysis. Based on the results of the analysis, it produces the level of physical vulnerability, the level of social vulnerability, the level of economic vulnerability and the level of environmental vulnerability, and then proposed directions for structural mitigation and non-structural mitigation based on the results of mapping the vulnerability of the area and directions for the development of the tidal flood disaster area in the Coastal Area, Balusu District, Regency Barru.